Low Fat Loss Response after Medium-Term Supervised Exercise in Obese Is Associated with Exercise-Induced Increase in Food Reward - Graham Finlayson; Phillipa Caudwell; Catherine Gibbons; Mark Hopkins; Neil King; John Blundell (Journal of Obesity)
Objective. To examine exercise-induced changes in the reward value of food during medium-term supervised exercise in obese individuals. Subjects/Methods. The study was a 12-week supervised exercise intervention prescribed to expend 500 kcal/day, 5 d/week. 34 sedentary obese males and females were identified as responders (R) or non-responders (NR) to the intervention according to changes in body composition relative to measured energy expended during exercise. Food reward (ratings of liking and wanting, and relative preference by forced choice pairs) for an array of food images was assessed before and after an acute exercise bout. Results. 20 responders and 14 non-responders were identified. R lost 5.2 kg ± 2.4 of total fat mass and NR lost 1.7 kg ± 1.4. After acute exercise, liking for all foods increased in NR compared to no change in R. Furthermore, NR showed an increase in wanting and relative preference for high-fat sweet foods. These differences were independent of 12-weeks regular exercise and weight loss. Conclusion. Individuals who showed an immediate post-exercise increase in liking and increased wanting and preference for high-fat sweet foods displayed a smaller reduction in fat mass with exercise. For some individuals, exercise increases the reward value of food and diminishes the impact of exercise on fat loss.